Jet‐triggered star formation in young radio galaxies. Issue 9 (1st November 2021) - Duggal, Chetna; O'Dea, Christopher; Baum, Stefi; Labiano, Alvaro; Morganti, Raffaella; Tadhunter, Clive; Worrall, Diana; Tremblay, Grant; Dicken, Daniel; Capetti, Alessandro
Abstract: Emission in the ultraviolet continuum is a salient signature of the hot, massive, and consequently short‐lived, stellar population that traces recent or ongoing star formation. With the aim of mapping star forming regions and morphologically separating the generic star formation from that associated with the galaxy‐scale jet activity, we obtained high‐resolution ultraviolet (UV) imaging from the Hubble Space Telescope for a sample of nine compact radio sources. Out of these, seven are known Compact Steep Spectrum (CSS) galaxies that host young, kiloparsec‐scale radio sources and hence are the best candidates for studying radio‐mode feedback on galaxy scales, while the other two form a control sample of larger sources. Extended UV emission regions are observed in six of the seven CSS sources showing close spatial alignment with the radio‐jet orientation. If other mechanisms possibly contributing to the observed UV emission are ruled out, this could be evidence in support of jet‐triggered star formation in the CSS phase of radio galaxy evolution and in turn of the "positive feedback" paradigm of host–active galactic nuclei interaction.